EFFECTIVENESS OF COOPERATIVE LEARNING MODEL NUMBERED HEADS TOGETHER (NHT) AND THINK PAIR SHARE (TPS) TOWARD STUDENTS MATHEMATICS LEARNING OUTCOMES - Liani Kusuma; Nur Arina Hidayati (Universitas Ahmad Dahlan, 2017)
learning of mathematics. The use of less appropriate learning model makes students less familiar with the material described by teachers and lead to poor learning outcomes mathematics. This study was included in experimental research that aims to determine the effectiveness of cooperative learning model NHT type cooperative learning model TPS. The population in this study were students of class VII SMP Muhammadiyah 3 Yogyakarta 2016/2017 academic year consisting of 8 classes. The sampling technique using random sampling techniques derived from class VII D as an experimental class I and VII E as experiment class II. The research instrument is the math achievement test in the form of multiple-choice questions. Test instruments include validity, distinguishing features, and reliability testing. Analysis of data using analysis prerequisite test consisting of a test for normality and homogeneity. Hypothesis test using t-test two parties and one party t-test. Based on the calculation of the t-test two parties with a significant level of 5%, and 58 degrees of freedom obtainedÂ , indicates that there are differences between the students' mathematics learning outcomes of students using cooperative learning model NHT with students who use cooperative learning model TPS in the second semester of seventh-grade students of SMP Muhammadiyah 3 Yogyakarta academic year 2016/2017. In the calculation of the t-test with a significance level of 5%, and 58 degrees of freedom obtained , shows that the cooperative learning model NHT more effective than cooperative learning model TPS to mathematics learning outcomes second semester of seventh-grade students of SMP Muhammadiyah 3 Yogyakarta academic year 2016/2017.